Review of Sevasti Trubeta (ed.), Special issue, Zeitschrift für Balkanologie 50/1 (2014) - Mergoupi-Savaidou, Eirini (Historein, 2017)
Sevasti Trubeta (ed.). Special issue, Zeitschrift für Balkanologie 50/1 (2014)